1982
DOI: 10.1677/joe.0.0940157
|View full text |Cite
|
Sign up to set email alerts
|

Daily variations in serotonin metabolism in the suprachiasmatic nucleus of the rat: influence of oestradiol impregnation

Abstract: In order to determine the temporal relationships between variations in 5-hydroxy-tryptamine (5-HT, serotonin) metabolism in the suprachiasmatic nucleus (SCN) and the cyclic LH surge, and also to check whether implantation of oestradiol capsules might modulate 5-HT metabolism in the SCN, we carried out a parallel study of 5-HT content in the SCN and median eminence, and 5-HT metabolism in the SCN and supraoptic region in vitro. These experiments were performed on intact male rats, ovariectomized females and ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
2

Year Published

1983
1983
1999
1999

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 0 publications
1
20
2
Order By: Relevance
“…However, they measured only the two points during 24 h. More values need to be observed at different points to characterize 5-HT and NE rhythms. Although we did not find any 5-HT rhythms in the SC, Hery et al (15) found a marked 5-HT rhythm in the SC at the beginning of the dark period.…”
Section: Discussioncontrasting
confidence: 99%
“…However, they measured only the two points during 24 h. More values need to be observed at different points to characterize 5-HT and NE rhythms. Although we did not find any 5-HT rhythms in the SC, Hery et al (15) found a marked 5-HT rhythm in the SC at the beginning of the dark period.…”
Section: Discussioncontrasting
confidence: 99%
“…Available data indicate a participation of the se rotoninergic mechanism in the positive feed-back effect of es trogen on LH secretion in prepubertal and adult female rats [7,8,11,12] suggesting that the serotoninergic system has an inhibitory effect on this mechanism [12]. On the other hand, 5-hydroxytryptophan (5-HTP) induces LH release in female prepubertal rats, but not in males [11].…”
mentioning
confidence: 99%
“…The facilitatory effect of 5HT occurs during a 'critical period' [6,10]; therefore, 5HT's influence upon the LH surge, like the surge itself, is linked in some way to the time of day. These quantitative and temporal perculiarities of 5HT's facilitatory effect on LH surges suggest that the daily pattern of 5HT synthesis and degradation, producing regu lar changes in its hypothalamic content [ 13,23], is function ally important.…”
mentioning
confidence: 99%